2019
DOI: 10.3390/ijerph16061080
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Knowledge about Sexually Transmitted Diseases (STDs): Implications for STDs Prevention and Care among Dermatology Patients in an Urban City in Vietnam

Abstract: Sexually transmitted diseases (STDs) are a substantial global burden of diseases, especially in developing countries. Lack of awareness of STDs may lead to a delay in treatment. This study aimed to assess knowledge about STDs and the associated factors among dermatological patients. A cross-sectional study was conducted among 622 patients at Vietnam National Hospital of Dermatology and Venereology (NHD). Structured questionnaires were used to investigate the knowledge about STDs. A multivariate Tobit regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 27 publications
6
43
1
5
Order By: Relevance
“…This nding was consistent with studies conducted among men who have sex with men [2,27]. This may be partly attributable to the extensive HIV and syphilis testing system in China, which may serve as a gateway for FSW to improve awareness of other STD, such as chlamydia and gonorrhea [14]. Meanwhile, the FSW who had HIV testing tended to have higher awareness of STD testing [28].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This nding was consistent with studies conducted among men who have sex with men [2,27]. This may be partly attributable to the extensive HIV and syphilis testing system in China, which may serve as a gateway for FSW to improve awareness of other STD, such as chlamydia and gonorrhea [14]. Meanwhile, the FSW who had HIV testing tended to have higher awareness of STD testing [28].…”
Section: Discussionsupporting
confidence: 87%
“…This may be partly attributable to the extensive HIV and syphilis testing system in China, which may serve as a gateway for FSW to improve awareness of other STD, such as chlamydia and gonorrhea [14]. Meanwhile, the FSW who had HIV testing tended to have higher awareness of STD testing [28]. Although there are many possible ways for promoting chlamydia and gonorrhea testing, such as home-based testing or self-collection [15], outreach services [29]and pay-it-forward [30], the effect is still not ideal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found that young Vietnamese prefer to download smartphone applications for disease prevention [88]. As a result, campaigns on the Internet and social media, and the use of online healthcare providers should be promoted to improve awareness of STIs [89]. Digital sex education is a potential solution for adolescents and youths together with the development of technology [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…Poor knowledge of the sequalae of CT infection could hinder the effectiveness of CT-related interventions such as screening [30], which could also explain the unwillingness to engage in PN in our study. Also, poor knowledge could contribute to an increase in risky behavior and thus increase the risk of STDs/HIV acquisition [35], and poor knowledge could also lead to delays in appropriate treatment [36]. Poor knowledge of STDs was seen in many studies [36][37][38][39] and is considered a major issue in disease prevention, so CT-related education, including information about complications, modes of transmission, and asymptomatic presentation, should be implemented in clinics to increase patient awareness and potentially facilitate PN.…”
Section: Discussionmentioning
confidence: 99%